2015
DOI: 10.1007/s00109-015-1335-6
|View full text |Cite
|
Sign up to set email alerts
|

Gremlin1 and chronic pancreatitis: a new clinical target and biomarker?

Abstract: Chronic pancreatitis (CP) is a progressive inflammatory condition triggered by the loss of exocrine pancreatic acini and fibrosis or scarring of pancreas tissue [1]. The exocrine pancreas comprises about 90 % of total pancreas and releases digestive enzymes such as chymotrypsin, amylase and lipase in response to a meal. CP develops in 16 % of patients presenting with acute pancreatitis, a number which increases to 38 % upon second admission. The most common symptom of CP is abdominal pain, which can be both in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Secreted active BMP4 can be inhibited at the extracellular level by interacting with secreted BMP4 antagonists such as GREM1 6 . High levels of Gremlin expression have been reported in neurons, alveolar epithelial cells, and goblet cells 17 and upregulation of GREM1 has been reported in fibrosis of the kidney, lung, heart, liver, and pancreas 18 . Immunohistochemistry performed on tissue microarrays has shown negative or weak GREM1 expression in the human esophagus 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Secreted active BMP4 can be inhibited at the extracellular level by interacting with secreted BMP4 antagonists such as GREM1 6 . High levels of Gremlin expression have been reported in neurons, alveolar epithelial cells, and goblet cells 17 and upregulation of GREM1 has been reported in fibrosis of the kidney, lung, heart, liver, and pancreas 18 . Immunohistochemistry performed on tissue microarrays has shown negative or weak GREM1 expression in the human esophagus 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Many experimental evidences suggest that Gremlin could be an important promoter of fibrosis in different pathologies, including liver fibrosis, lung diseases (particularly pulmonary hypertension and idiopathic pulmonary fibrosis), myocardial fibrosis, and chronic pancreatitis ( Khokha et al, 2003 ; Mueller et al, 2013 ; Brazil, 2015 ; Mezzano et al, 2018 ). In several human renal diseases, Gremlin was found overexpressed, mainly in areas of tubulointerstitial fibrosis ( Murphy et al, 2002 ; Dolan et al, 2005 ; Carvajal et al, 2008 ), suggesting that Gremlin could be involved in the fibrotic process during CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies demonstrate an important role of Gremlin in development, including nephrogenesis, acting as a BMP antagonist ( Merino et al, 1999 ; Khokha et al, 2003 ; Michos et al, 2004 ). More recently, Gremlin has been suggested as an important promoter of fibrosis in different pathological conditions including renal, liver, lung, and myocardial diseases ( Dolan et al, 2005 ; Carvajal et al, 2008 ; Mueller et al, 2013 ; Brazil, 2015 ; Erdmann et al, 2015 ; Mezzano et al, 2018 ). Moreover, in vitro studies have demonstrated direct effects of Gremlin in the regulation of profibrotic-related events ( Zode et al, 2009 ; Li et al, 2012 ; Rodrigues-Diez et al, 2012 ; Huang et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…32, 33 We therefore used PLGA, a state-of-the-art material for drug delivery, to load the drug. 16,17 To enhance the drug delivery efficiency, the particles are therefore modied by PEG via biotin-avidin reactions (Fig. 16,17 To enhance the drug delivery efficiency, the particles are therefore modied by PEG via biotin-avidin reactions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we employ PEGylated poly(lactic-co-glycolic acid) (PLGA) nanoparticles, a state-of-the-art material for drug delivery, 14,15 to improve the delivery efficiency and bioavailability of apigenin for CP treatment. Considering the signicant challenge, that there is currently no active target for CP treatment, 16,17 the particle surface was modied using PEGylation to enhance its in vivo circulation time and delivery efficiency. Studying at a cellular level nds that apigenin loaded nanoparticles can inhibit PSC proliferation and induce PSC apoptosis.…”
Section: Introductionmentioning
confidence: 99%